High-Bandpass Filters in Electrocardiography: Source of Error in the Interpretation of the ST Segment. (21st June 2012) - Buendía-Fuentes, F.; Arnau-Vives, M. A.; Arnau-Vives, A.; Jiménez-Jiménez, Y.; Rueda-Soriano, J.; Zorio-Grima, E.; Osa-Sáez, A.; Martínez-Dolz, L. V.; Almenar-Bonet, L.; Palencia-Pérez, M. A.
Abstract : Introduction . Artifactual variations in the ST segment may lead to confusion with acute coronary syndromes. Objective . To evaluate how the technical characteristics of the recording mode may distort the ST segment. Material and Method . We made a series of electrocardiograms using different filter configurations in 45 asymptomatic patients. A spectral analysis of the electrocardiograms was made by discrete Fourier transforms, and an accurate recomposition of the ECG signal was obtained from the addition of successive harmonics. Digital high-pass filters of 0.05 and 0.5 Hz were used, and the resulting shapes were compared with the originals. Results . In 42 patients (93%) clinically significant alterations in ST segment level were detected. These changes were only seen in "real time mode" with high-pass filter of 0.5 Hz. Conclusions . Interpretation of the ST segment in "real time mode" should only be carried out using high-pass filters of 0.05 Hz.